Polyurethane (PU) based multifunctional materials: Emerging paradigm for functional textiles, smart, and biomedical applications. Issue 38 (10th August 2022) - Sikdar, Partha; Dip, Tanvir Mahady; Dhar, Avik K.; Bhattacharjee, Maitry; Hoque, Md. Saiful; Ali, Solaiman Bin
Abstract: The advances in polymer chemistry research have revolutionized the field of smart materials and biomedical. Polyurethanes (PUs) are a versatile polymer class with diverse structure, morphology, and behavior under various conditions deemed suitable for many functional and intelligent responses. Owing to their biocompatibility, biodegradability, excellent mechanical strength, tailorable chemical, and physical forms, PU has drawn significant research attention in recent times for a wide range of applications. Herein, this review paper outlines PU's recent advances in specific applications encompassing functional textiles, intelligent functionality and medical usage. This article contains a comprehensive review of recent developments and research works concerning PU's direct involvement as coatings, 3D objects, or composite parts to add novel purpose to the textile substrates, smart objects, or medical applications. Commencing with PU's application for the waterproof breathable textiles, the review further explores recent research where PU was incorporated as a phase change material and protective clothing. This review further delves innovative functionalities and responsiveness of the polymer triggered by various stimuli. It ends with an inclusive review of PU's different forms of application concerning medical devices and activities. Finally, perspectives on future challenges and new research opportunities are also presented and discussed. Abstract :